Implementación De Una Filosofía De Mejora Continua En Una Organización Privada De Servicios - Valdéz, Gabriela Alejandra (European Scientific Journal, ESJ, 2016)
We report about the implementation of the philosophy of continuous improvement with Transactional Analysis in a private services institution, in order to incorporate the best possible practices and a process of continuous improvement, including the discovery of unknown personal potentials. This positive philosophical change in the culture of the organization, allows us to apply a plan for the development of people, engaging all the staff of the company. According to the specific needs of the company, we developed a set of social activities, including seminars, workshops, brainstorming sessions. The main activity is to promote creativity as part of the work culture.